2010
DOI: 10.1002/jez.644
|View full text |Cite
|
Sign up to set email alerts
|

Thermal constraints for range expansion of the invasive green mussel, Perna viridis, in the southeastern United States

Abstract: Cold temperatures are thought to be among the most important determining factors of geographic distribution for tropical and sub-tropical marine invertebrates. The Asian green mussel, Perna viridis, has been introduced into coastal waters of Florida where its current distribution is hypothesized to be limited by low temperatures during winter. Lethal and sub-lethal effects (heat shock protein/Hsp70 expression) of cold water and air temperatures were analyzed in two size classes of P. viridis from Florida in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 42 publications
3
26
1
Order By: Relevance
“…Such knowledge was crucial to determining the impact of temperature variation on the metabolism and immune-related functions of hemocytes. In accordance with the very recent work of Urian et al [22], our results showed that relatively low temperature (10 C) represents a stressful condition for the Floridian green mussels, as depicted by the low phagocytic capacity and the increase of oxidative metabolism. Then, as suggested by Urian et al [22], in the current environmental conditions, green mussels might have already reached the Northern edge of their distribution in the USA.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Such knowledge was crucial to determining the impact of temperature variation on the metabolism and immune-related functions of hemocytes. In accordance with the very recent work of Urian et al [22], our results showed that relatively low temperature (10 C) represents a stressful condition for the Floridian green mussels, as depicted by the low phagocytic capacity and the increase of oxidative metabolism. Then, as suggested by Urian et al [22], in the current environmental conditions, green mussels might have already reached the Northern edge of their distribution in the USA.…”
Section: Discussionsupporting
confidence: 93%
“…The populations of green mussels from Florida were, until now, almost exclusively studied for their geographic distribution patterns, in order to understand their origin and to predict the population dynamics [1e4]. Very recently, Urian et al [22] investigated on the effects of seawater temperature on the survival of Floridian P. viridis, and concluded that due to a weak low temperature resistance, green mussels might have already reached the Northern edge of their distribution in USA. Indeed, temperature is a predominant factor determining the geographic distribution of marine invertebrates [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But for each site of niches we were got the speciments as sample only that representative in lifestyle and feeding behavior. (Urian, 2009). The colony of Mytilus sp is a very solid and tight.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, during 2005, wild adult populations of P. canaliculus at Banks Peninsula suffered high rates of mortality during a 3day heat wave event where air temperatures reached 36°C (Petes et al, 2007). Such thermally induced mortality is not restricted to elevated temperatures, with sudden drops in water and air temperature producing significant mortality in adults and juveniles of the green mussel, P.viridis (Firth et al, 2011;Urian et al, 2011). Temperature variations are predicted to increase in magnitude and frequency with the progression of climate change (Rahmstorf and Coumou, 2011) and further highlight the complex interplay between biotic (e.g.…”
Section: Discussionmentioning
confidence: 99%